Comparison of the efficacy of tibial transverse transfer and periosteal distraction techniques in the treatment of diabetic foot refractory ulcers - Yang, Yang; Chen, Fang; Chen, Yiguo; Wang, Wei (Frontiers in Surgery, 2024)
ObjectiveTo investigate the efficacy of comparing tibia transverse transport (TTT) and periosteal distraction in treating diabetic foot ulcers.MethodsA retrospective analysis of 19 patients with diabetic foot ulcers treated with both procedures between February 2020 and November 2022, 8 of whom were treated with the tibial transverse transfer technique (transfer group) and 11 with the osteochondral distraction technique (distraction group), was performed to compare and analyze the clinical efficacy of the two methods.ResultsAll wounds were healed in both groups, and the healing time ranged from 15 to 41days with a mean of 28d. The limb preservation rate was 100%. The operative time, intraoperative bleeding, and pain score in the operative area were significantly less in the distraction group than in the removal group, with statistically significant differences (P < 0.05). Intra-group comparison between the two groups of patients after surgery revealed that the skin temperature, ABI, TcPO2, SWM and VAS of the affected limb were significantly improved compared with those before surgery, and the difference was statistically significant (P < 0.05). The expression levels of VEGF, bFGF, EGF and PDGF were significantly higher than before surgery in both groups, and the difference was statistically significant (P < 0.05). No statistically significant differences were found in skin temperature, ABI, TcPO2, SWM, VAS, VEGF, bFGF, EGF and PDGF between the two groups at the corresponding time points preoperatively and postoperatively (P > 0.05).ConclusionsThe Periosteal distraction technique can significantly promote the healing of diabetic foot ulcers. It has the same efficacy as TTT in promoting the healing of diabetic foot ulcer wounds and improving the peripheral circulation of affected limbs. In addition, the periosteal distraction technique has the advantages of small trauma, simple operation, few complications, and convenient nursing care.